Choose wisely: intrinsic motivation for enrollment is associated with ongoing intrinsic learning motivation, study success and dropout. Issue 1 (2nd January 2023) - Messerer, Laura A. S.; Karst, Karina; Janke, Stefan
ABSTRACT: Student dropout is a frequent phenomenon in higher education institutions that entails high costs for individuals, institutions, and society as a whole. Thus, it is crucial to identify protective factors regarding dropout in cases in which it could have been prevented. In line with Person-Environment Fit Theory, we assume that intrinsic motivation for enrollment (i.e. choice of major based on personal interests) is an important protective factor that facilitates intrinsic learning motivation over time, which should in turn be positively associated with performance at university and negatively associated with dropout (intentions). We tested these assumptions in two longitudinal studies using structural equation modeling. In study 1, we found that intrinsic motivation for enrollment was associated with a positive development of intrinsic learning motivation ( N  = 774 students, two time points during the first two semesters). In study 2, we investigated whether intrinsic learning motivation mediated the association between intrinsic motivation for enrollment and study success variables ( N  = 1185 students, three time points during the first academic year). Intrinsic motivation for enrollment was only slightly positively associated with university GPA, but negatively with students' dropout intention measured one year later – mediated via intrinsic learning motivation. We did not find an association between intrinsic motivation for enrollment and actual dropout. The presented research provides the foundation for a process model linking the quality of motivation for enrollment to study success, which has strong implications for counseling of prospective students as well as for the identification of students at risk.